Workplace wellness: industry associations are well placed and some are ready to take a more active role in workplace health - Geraldine Marsh; Virginia Lewis; Jenny Macmillan; Su Gruszin (BMC, 2018)
Abstract Background Investments in settings-based health interventions can include workplaces, however, engaging with businesses and convincing them to take a role can be difficult. Our research investigated the potential for trade or industry associations (IAs) to have a role in promoting workplace health initiatives to their members. Methods Seventeen semi-structured interviews were undertaken with senior executives from IAs representing industries in the mining, transport, agriculture, manufacturing, farming, hospitality, and construction sectors. Analysis of interviews identified themes around attitudes to workplace health promotion programs and the perceived, actual and potential role/s of IAs in promoting workplace wellness. Results IA representatives believed workplaces had potential to be promoting the health and wellbeing of workers through their member organisations; however for some the extent of their role was unclear and for others there was confusion between government-mandated safety initiatives and non-mandated health and wellbeing initiatives. All reported that their IA could have a role in promoting worker health and wellbeing initiatives to member organisations. IAs with larger companies as members were more likely to recognise the importance of workplaces promoting workers' health; however, the degree of involvement considered appropriate varied. Most IAs had not discussed the topic with their member organisations although they identified resources and support that could assist them in encouraging members to undertake workplace health programs. Resources included industry-relevant business cases outlining the benefits of workplace health, and industry-appropriate worker health information. Conclusions Our research suggests that across many industry sectors, larger IAs in particular are ready to take a more active role in workplace health initiatives and are well placed to promote these to member organisations.